Leukocyte telomere length change in children with obesity in the context of an isocaloric fructose restriction intervention - Janet M. Wojcicki; Elissa Epel; Jue Lin; Viva Tai; Jean-Marc Schwarz; Susan M. Noworolski; Ayca Erkin-Cakmak; Kathleen Mulligan; Alejandro Gugliucci; Rob H. Lustig (Diabetology & Metabolic Syndrome)
Abstract Background Few studies have evaluated changes in leukocyte telomere length (LTL) over a short time period (e.g. 1 week). LTL shortening is accelerated by exposure to inflammation and reactive oxygen species (ROS) damage. Methods In the context of an isocaloric fructose restriction study that was conducted with 43 Black and Latinx children over a 9-day period, we evaluated the relationship between metabolic health at baseline and metabolic changes and LTL at baseline and %LTL change over the follow-up period. Linear regression models were used to assess associations between metabolic correlates and LTL at baseline and LTL changes over 9 days. Results Overall children lost − 0.05 ± 0.14 T/S units or − 2.98 ± 8.74% total change over the follow-up period. Higher concentrations of HDL-C, APO-AI and a greater % of large HDL-C at baseline were associated with reduced LTL attrition rates at day 10 (p < 0.01; p < 0.01 and p = 0.02 respectively). Increases in APO-AI over the follow-up period were associated with increased LTL attrition over the follow-up period (p = 0.03). Conclusions In this short term isocaloric fructose restriction study, LTL at baseline and changes in LTL over 9 days were associated with HDL-C and APO-AI and not with any other non-HDL-C lipids. Additional, larger studies are necessary to better understand the interplay between short term fructose restriction, LTL changes and HDL-C/APO-AI.